WORK MOTIVATION: CAREER DEVELOPMENT AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE - Mu'amar Fiqri Alazhar; Dina Lusianti; Agung Subono (Universitas Wahid Hasyim Semarang, 2023)
This research aims to analyze the influence of career development on Employee Performance at CV. Mubarokfood Cipta Delicia. Analyzing the influence of Organizational Commitment on Employee Performance at CV. Mubarokfood Cipta Delicia. Analyzing the influence of Career Development on Work Motivation at CV. Mubarokfood Cipta Delicia. Analyzing the influence of Organizational Commitment on Work Motivation at CV. Mubarokfood Cipta Delicia. Analyzing the influence of Work Motivation on Employee Performance at CV. Mubarokfood Cipta Delicia. The approach used in this research is quantitative. The sample was 126 employees at CV. Mubarokfood Cipta Delicia and sampling use purposive sampling technique. The data collection technique used in this research was a questionnaire. The data analysis technique uses SEM-AMOS. The results of this research show that Career Development has a positive and not significant effect on Employee Performance at CV. Mubarokfood Cipta Delicia. Organizational Commitment has a significant positive effect on Employee Performance at CV. Mubarokfood Cipta by Delicia. Career Development has a significant positive effect on Work Motivation at CV. Mubarokfood Cipta Delicia. Organizational Commitment has a positive and not significant effect on Work Motivation. Work Motivation has a positive significant effect on Employee Performance. Work Motivation is unable to mediate the relationship between Career Development variables and Employee Performance. Work Motivation is unable to mediate the relationship between the Organizational Commitment variable and Employee Performance.